PENGARUH SISTEM PENGENDALIAN INTERNAL TERHADAP KETEPATAN WAKTU LAPORAN KEUANGAN PEMERINTAH DAERAH PADA KANTOR BADAN PENGELOLAAN KEUANGAN PENDAPATAN DAN ASET KABUPATEN BENER MERIAH - Denny Firmansyah; Tri Harnida Dewi (Jurnal Inovasi Penelitian, 2020)
This study discusses how to determine the internal control system for the timeliness of local government financial reporting. This research was conducted at the Office of the Financial, Income and Asset Management Agency of Bener Meriah Regency. The number of samples in this study were 64 respondents who were selected based on saturated sampling (census) techniques. The data in this study were obtained through investigation and processed with the help of the SPSS version 22 program. Based on the results of data analysis using simple linear regression produces a tcount = 10.841> ttable = 1.669 with a significant number of 0.000 so that the system can be accessed by local government finances. The coefficient of determination in this study amounted to 0.655 or 65.5%. This shows that the positive internal control system variable on the timeliness of financial reporting is 65.5% while the remaining 34.5% is needed by other factors not related in this study